?FLOTATION CHARACTERISTICS OF LEAD-ZINC ORE FROM BESHAM, DISTRICT SWAT, NWFP, PAKISTAN (Biological Sciences - PJSIR, 2000)
Metallurgical grade concentrates of lead and zinc, each assaying over 50% metal content, have been produced by two stage flotation from 8esham lead-zinc ore. The ore consists of mainly galena (PbS) and sphalerite (ZnS) as economic minerals while Fe-sulphide/oxide, quartz and other silicates are the gangue minerals. The average concentration of galena and sphalerite in head sample is 0.86% and 9.97% respectively. Both galena and sphalerite can be recovered at a feed size of 85-90% passing 74 microns (wet grinding along with 0.5 kg r' of sodium cyanide) with pulp density of25% solids. Galena is recovered as a first step by adjusting pulp pH at 9 with lime. Potassium ethyl xanthate is used as collector and 0-250 (polypropylene glycol) as frother. The recovery of sphalerite is made by activation with the help of copper sulphate at pH IIwith the same operational condition as that of galena. The final recoveries are over 90% of Lead and zinc from the ore.